PERAN CORPORATE SOCIAL RESPONSIBILITY (CSR) UNTUK PENINGKATAN EKONOMI MASYARAKAT DI KELURAHAN WATUSAMPU - Muhammad Zidan; Malkan; Muhammad Syafaat (Program Studi Akuntansi Syariah Fakultas Ekonomi dan Bisnis Islam UIN Datokarama Palu, 2025)
Corporate Social Responsibility is a company's activity to be responsible for achieving profit, community welfare, and environmental sustainability. This research uses a qualitative approach, data collection techniques through interviews, observations, and documentation studies, and the data analysis techniques used are data reduction, data presentation, and conclusion drawing. The research results show that the implementation of Corporate Social Responsibility at PT. Hasal Logam Utama in Watusampu Village, Ulujadi District, is developed in the form of social responsibility towards the environment, social responsibility towards fair operational practices, social responsibility towards community involvement and development, and social responsibility towards corporate governance. The concept of CSR in Islam is the concept of zakat; Islamic economic law has long regulated a company's responsibilities, but in this case, it is depicted in the form of zakat.